OPTIMIZATION OF SODIUM DODECYL SULPHATE AS A FORMAZAN SOLVENT AND COMPARISON OF 3-(4,-5-DIMETHYLTHIAZO-2-YL)-2,5-DIPHENYLTETRAZOLIUM BROMIDE (MTT) ASSAY WITH WST-1 ASSAY IN MCF-7 CELLS - Endah Puji Septisetyani; Ratih Asmana Ningrum; Yulaika Romadhani; Popi Hadi Wisnuwardhani; Adi Santoso (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
A 3-(4,-5-dimethylthiazo-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay is a method that used to measure cell viability. It is based on the conversion of MTT by succinic dehydrogenase enzyme into insoluble formazan. Dissolution of formazan by using proper solvent is the most important step of MTT assay to obtain valid and reliable data. In this study, we observed several solvents [isopropanol, dimethyl sulfoxide (DMSO), and sodium dodecyl sulphate (SDS)] to validate MTT assay by using MCF-7 cells. The observation was performed by MTT addition at concentration of 0.5µg/µL, 3-4h cells incubation at 37°C, dissolution of formed formazan crystal and absorbance measurement at 570nm. The result showed that formazan completely dissolved in DMSO and 10% SDS. The most advantage of using SDS was it avoided the removal of partially dissolved formazan. In this observation, we also found that pH was a very important factor in SDS solution that affected the reaction. The use of optimal condition on MTT assay by SDS-0.01M HCl and SDS-0.025M HCl as formazan solvents showed that IC50 of curcumin were 32.3±0.78µM and 24.08±1.72µM respectively, while WST-1 assay resulted IC50 of curcumin 80.69±5.35µM. Altogether, this study strongly indicated that SDS-0.01M HCl was the best formazan solvent for MTT assay.